(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to develop an instrument to improve conceptual understanding of number operation materials owned by prospective teachers at IKIP PGRI Pontianak. This research is a development research. The subjects in this study are students in the third semester of the Mathematics Education Study Program, Faculty of Education, Mathematics and Technology, as many as 20 students who were randomly selected. The main instrument is the researcher himself, while the supporting instruments are the task of number operation problems and interview guidelines. Data analysis is carried out descriptively on all data obtained. The results of the analysis show that the form and type of learning instrument that is suitable for improving students’ conceptual ability, especially in the interpretation ability in number operation material, is a multiple-choice sample problem unit. Students’ interpretation skills in number operations material are not good because they still have the opportunity to understand and apply the concept of operations on numbers. Learning instruments in the form of units of multiple-choice questions of the second type are practical to be applied with the aim of improving students’ conceptual abilities, especially interpretation skills in number operation materials